AN ENGINEERED SYSTEM FOR SOLID WASTE COLLECTION IN SAMARU, ZARIA, NIGERIA - Tivde, Terna Nathaniel; Ibrahim, Fatima Badiru; Igboro, Sunday Bamidele; Igbebe, Samson (FUDMA JOURNAL OF SCIENCES, 2024)
Solid waste includes all materials that are firm and stable in shape including semisolid materials that are no longer considered of sufficient value to be retained in a given setting. Solid waste generation rates and patterns within the study area were mapped out through GPS, Google route software, AutoCAD, ArcGIS, GPS, Route optimization software, measuring tape, Marker, Containers of equal volume, Record book, Calculator, and Stopwatch. Eleven sacks were used to collect solid waste from eleven different households daily within three months of the wet and dry seasons of the year. The highest average volume of solid waste generated per household per week in Samaru was in the dry season =0.25 m3. The dry season witnesses a substantial volume of 0.206 m³ for garbage organic materials, constituting 66.45% of the total composition. In the wet season, this volume remains significant at 0.104 m³, accounting for 61.18% of the total composition. The highest percentage of organic materials (garbage) during both seasons suggests a need for improved organic waste management. The minimum allowable capacity of the solid waste collection containers for the designed system is 10 m3 considering a minimum of two containers per city block